Sifat Mekanis dan Struktur Mikro Pengelasan Gesek Baja Tahan Karat Austenitik AISI 304 - ARIS WIDYO NUGROHO, TOTOK SUWANDA, FEBRI IRWANTO (2014)
The aim of this study is to investigate experimentally the microstructural properties and welding strengths of the friction welded joints using austenitic stainless steel (AISI 304) base metal. The experiments were carried out using a beforehand designed and constructed experimental friction welding set-up. Firstly, the welding experiments were under different friction pressure (1,38-4,14 MPa) and upsetting pressure (6,90-8,27 MPa). Later, the strengths of the joints were examined by tension test and the results were compared with those of the base metals. Microstructures in the interfaces of the joints were also obtained and examined. The results show that porosities were observed in bondline zone for all specimens. As the friction pressure increased, the fully plastically deformed zone becomes increased. Tensile test results indicated that, generally the joint strength is increased with an increase of the friction pressure and the upsetting pressure. The friction welded joint strenght were found to be lower than that of the base metal. The detailed fractographic observation confirmed that the brittle rupture occurred at the joint zone.